Canonical Wnt Signaling Regulates Extracellular Matrix Expression in the Trabecular Meshwork - Villarreal, Guadalupe (Invest Ophthalmol Vis Sci, 2014)
PURPOSE. Canonical Wnt signaling has emerged as a critical regulator of aqueous outflow facility and intraocular pressure (IOP). In this study, we examine the role of canonical Wnt signaling on extracellular matrix (ECM) expression in the trabecular meshwork (TM) and explore the molecular mechanisms involved. METHODS. β-catenin localization in human TM tissue was examined using immunofluorescent staining. Primary human TM cells were incubated with lithium chloride (LiCl) and the effect on active β-catenin expression was assessed by immunoblot. Adenovirus expressing a dominant-negative TCF4 mutant that lacks a β-catenin binding domain was used. Changes in the levels of the microRNA-29 (miR-29) family and ECM proteins were determined by real-time quantitative PCR and immunoblot analysis, respectively. RESULTS. β-catenin was expressed throughout the TM, with localization primarily to the plasma membrane. Incubation of TM cells with lithium chloride increased the expression of active β-catenin. Lithium chloride treatment upregulated miR-29b expression, and suppressed the levels of various ECM proteins under both basal and TGF-β2 stimulatory conditions. Infection of TM cells with a dominant-negative TCF4 mutant induced ECM levels without a significant change in the expression of the miR-29 family. CONCLUSIONS. Collectively, our data identify the canonical Wnt signaling pathway as an important modulator of ECM expression in the TM and provide a mechanistic framework for its regulation of outflow facility and IOP.